Implementation of Cognitive Theory in Developing Measurement Learning Multimedia for Deaf Students - I Made Suarsana; I Gde Wawan Sudatha; Gusti Ayu Mahayukti; I Wayan Edy Ari Suandana; I Gusti Putu Suharta (Universitas Pendidikan Ganesha, 2021)
The implementation of cognitive theory in multimedia development for deaf students (students with visual channels only) would be re-examined for its effectiveness. This study aimed to develop mathematics-learning multimedia based on cognitive theory for deaf students on